High Speed Internet Development in Africa Using 4GLTE Technology-A Review - Nj, Mohamed; S., Shahrin; S., Nanna; Fairuz Iskandar Othman, Mohd (Bulletin of Electrical Engineering and Informatics, 2019)
African continent is ranked second biggest world’s regions populated and having a huge amount of natural resources to be locally transformed or outsourced overseas for this purpose. The traditional telecommunications system helped connect people and enabled them managing business and trading in Africa for long-time; many African countries got embarked early into some process of changing their network and technology systems during the first years of the information age. Over few decades ago, the introduction of the new telecom methods and techniques influenced much African countries’ growth on different perspectives. The situation triggered in people an interest and curiosity. They analyzed the factors supporting such changes, which in the case of this paper is all about the advent and adoption of LTE/4GLTE technologies including its services commercialization in Africa. This articles review attempts to draw up an overview of 4GLTE networks technologies and its internet; it includes the current evolution of telecom’s networks within and even beyond African continent, assisted by 4GLTE expansion. An extended view is provided throughout this article’s development with respect to what could be expected (or is missing) for the sake of this continent’s telecom’s infrastructures enhancement and a better QoS to Africa’s dwellers.